Corporate Social Responsibility dan Orientasi Pasar Peranannya dalam Meningkatkan Kinerja Bisnis Perusahaan (Studi pada Perusahaan AMDK di Jawa Timur) - Christin Susilowati; MS. Idrus; Armanu Thoyib (Jurnal Aplikasi Manajemen, 2012)
In the debate context of Corporate Social Responsibility (CSR), there are two different views. Firstly, as the main objective of any businesses is profit, CSR is considered as financial burden to the company. On the other hand, the second view proposes that profit-oriented companies tend to be unsustainable if the interests of relevant stakeholders are not considered. The claim that there is a relationship between CSR and business performance is still debatable. CSR can be properly and effectively implemented if companies use a systematic approach to address issues related to the environment. The company’s market orientation is a manifestation of sensitivity and response to the company’s stakeholders. Thus, businessoriented market will try to integrate the needs of the social responsibility into each company’s activities. In this study, the impact of market orientation and CSR on corporate performance was proposed to take place through the process of building reputation and employees’ commitment. This study aims to examine the relationship between CSR and market orientation, and explore relationships with the company’s reputation and employees’ commitment in increasing business performance. 30 bottled drinking water companies in East Java were chosen. Partial Least Square analysis (PLS) was employed due to the limited number of respondents. The findings suggest that the impact of CSR and market orientation on a firm’s performance is determined by the mediating variable, corporate reputation and employees’ commitment. Stronger implementation of market orientation and CSR is proved to build a better company reputation. Implementation of market orientation, CSR and reputation of the company is proved to strengthen employees’ commitment to the company. Implementation of market orientation and CSR is not able to improve the company performance, if when implemented, the company was not able to effectively communicate the implementation to build company’s reputation and increase employees’ commitment to the company.Keywords: CSR, Market Orientation, Corporate Reputation, Employee Commitment and Business Performance.